أثر البرمجيات في جودة خدمات المصرف التجاري السوري دراسة ميدانية في فروع المصرف التجاري في محافظة طرطوس - حيدر, عز الدين; وقاف, يوسف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research aims to identify the impact of the software and its role in improving the quality of the services provided in Syrian Commercial Bank and its branches in Tartous Governorate, used data was obtained from a questionnaire designed by the researcher. The search reached many results, the most important of which: - The suitability of software with business requirements contributes to improving the quality of commercial banking branches services. - Software compatibility with hardware contributes to improving the quality of services at the Syria Commercial Bank. - To develop software cadres constantly contributes to improving the quality of the services of the Syria Commercial Bank. The researcher concluded with a number of recommendations, the most important of which are: - To activate the role of computer software in banking, which is of great importance in the good impact on quality services for commercial banks - Conduct periodic studies on computer software provided at banks in order to assess their ability to improve the quality of commercial banking branches services. تهدف هذه الدراسة إلى التعرف على أثر البرمجيات ودورها في تحسين جودة الخدمات المقدمة في المصرف التجاري السوري وفروعه في محافظة طرطوس، وذلك من خلال بيانات تم الحصول عليها بواسطة استبانة صممها الباحث. توصل البحث إلى جملة نتائج أهمها: - يسهم تناسب البرمجيات مع متطلبات العمل في تحسين جودة خدمات فروع المصرف التجاري. - يسهم توافق البرمجيات مع الأجهزة في تحسين جودة الخدمات في المصرف التجاري السوري. - يسهم تطوير كوادر البرمجيات باستمرار في تحسين جودة خدمات المصرف التجاري السوري. وخلص الباحث إلى مجموعة من التوصيات أهمها: - العمل على تفعيل دور البرمجيات الحاسوبية في الأعمال المصرفية، لما له من أهمية بالغة في التأثير الجيد على جودة الخدمات المصارف التجارية السورية. - إجراء دراسات دورية عن البرمجيات الحاسوبية المقدمة في المصارف بغية تقييم قدرتها على تحسين جودة الخدمات لفروع المصرف التجاري السوري.